2010
DOI: 10.1007/s11064-010-0205-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Flavonoids Against Oxidative Stress Induced by Simulated Microgravity in SH-SY5Y Cells

Abstract: Many lines of evidence suggest that microgravity results in increased oxidative stress in the nervous system. In order to protect neuronal cells from oxidative damage induced by microgravity, we selected some flavonoids that might prevent oxidative stress because of their antioxidant activities. Among the 20 flavonoids we examined, we found that isorhamnetin and luteolin had the best protective effects against H(2)O(2) or SIN-1-induced cytotoxicity in SH-SY5Y cells. Using a clinostat to simulate microgravity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…Wang et al also reported the protective effects of NAC on ROS production and cell senescence under SMG treatment (Wang et al 2009). Qu et al showed that antioxidants, isorhamnetin and luteolin, could protect neuroblastoma SH-SY5Y cells against microgravity-induced oxidative stress (Qu et al 2010). These results indicate that antioxidants such as NAC might be used in the protection of ROS stress induced by the combined effects of SMG and other factors of space environment, which may provide valuable strategy for health protection in manned space exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al also reported the protective effects of NAC on ROS production and cell senescence under SMG treatment (Wang et al 2009). Qu et al showed that antioxidants, isorhamnetin and luteolin, could protect neuroblastoma SH-SY5Y cells against microgravity-induced oxidative stress (Qu et al 2010). These results indicate that antioxidants such as NAC might be used in the protection of ROS stress induced by the combined effects of SMG and other factors of space environment, which may provide valuable strategy for health protection in manned space exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several lines of evidence showed that SMG increased ROS production in some cell types, such as the PC12 cells, SH-SY5Y cells, and MEF cells (Wang et al 2009; Qu et al 2010; Li et al 2015). It has been reported that SMG delayed the rejoining of double-strand breaks (DSBs) induced by IR and increased the genotoxic effects of IR (Mognato et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Clinorotation was performed at 30 rpm (revolutions per minute) according to previous studies (Dai et al 2000;Qu et al 2010), having 3 specially designed flasks with an internal diameter of 4 cm in each group. Glass slides were inserted into a specially designed shelf in every flask.…”
Section: Clinorotationmentioning
confidence: 99%
“…Many lines of evidence suggest that conditions experienced during microgravity result in increased oxidative stress1011. Indo et al .…”
mentioning
confidence: 99%